OP0178 IMAGING NEOANGIOGENESIS IN RHEUMATOID ARTHRITIS (INIRA): WHOLE-BODY SYNOVIAL UPTAKE OF A 99MTC-LABELLED RGD PEPTIDE IS HIGHLY CORRELATED WITH POWER DOPPLER ULTRASOUND. (2nd June 2020) - Attipoe, L.; Subesinghe, S.; Blanco-Gil, C.; Opena, M.; Rosser, M.; Cook, G.; Cope, A.; Garrood, T.
Abstract : Background: Power Doppler ultrasound (PDUS) is superior to clinical examination in detecting synovitis in patients with rheumatoid arthritis (RA). Although dynamic and cheap it is impractical to scan large numbers of joints in routine clinical settings. MRI, whilst sensitive for synovitis, is expensive and routine use is limited to targeted joints. Bone scintigraphy produces whole body images but due to limited specificity is not routinely used. 99m Tc-maraciclatide (Serac Healthcare) is a radiolabelled tracer which binds with high affinity to integrin αv β3, a cell-adhesion molecule up-regulated on neoangiogenic blood vessels. It therefore has the potential to image synovial inflammation at the whole-body level. We previously showed in a pilot study that uptake was seen in the inflamed joints of five RA patients and that this correlated with PDUS. This study explores correlation with PDUS in a larger groups of patients with varied disease activity. Objectives: To determine the correlation between ultrasound and 99m Tc-maraciclatide imaging in patients with rheumatoid arthritis. Methods: 50 patients with RA fulfilling ACR 2010 classification criteria were recruited. Patients underwent an ultrasound scan of 40 joints with grey scale (GS) and PD quantification. Each joint was scored on a scale of 0-3 for GS and PD with a total score calculated for each patient. Within 3 hours of the ultrasound patients were injected with 740 MBq of 99m Tc-maraciclatide. Using a gamma camera, whole body planar views and dedicated hand and foot views were taken 2 hours after injection (Figure 1). Acquisition time was 20 minutes for whole body and 20 minutes for hand and foot views. 99m Tc-maraciclatide images were scored as positive or negative uptake for each joint (binary score). A quantitative score was also calculated for each joint where there was uptake with this corrected for background uptake. Total binary and quantitative scores per patient were calculated. Ultrasound and 99m Tc-maraciclatide scores were tested for correlation with Pearson's correlation coefficient (r). Interrater agreement for 2 scorers was calculated using kappa (ĸ) and concordance correlation coefficient ( Pc ). Results: Strong correlation was seen when total PDUS was compared to binary scores (r=0.92, r 2 =0.85) (Figure 2 ) and quantitative scores (r=0.85, r 2 =0.72). ĸ was 0.82 and 0.79 for binary and ultrasound scores respectively. Pc was 0.82 for quantitative scores. p was <0.0005 for all results. 99m Tc-maraciclatide uptake was also seen in inflamed tendons/tendon sheaths. The imaging procedure was well-tolerated. There were no tracer-related adverse events. Conclusion: 99m Tc-maraciclatide uptake was highly correlated with PDUS highlighting its potential as an alternative imaging modality. 99m Tc-based planar imaging has the unique capacity to image the whole body and hence the total synovial inflammatory load in a quick acquisition. The imaging equipment to perform these scans is already widely available in radiology departments. Interpretation of scans is also much simpler compared to US/MRI. It could therefore have a role in key decision-making points in pathways for diagnosis, treatment failure, and remission prior to dose tapering. Disclosure of Interests: None declared